ANALISIS STRUKTUR ATAS GEDUNG WISMA MULYA BUKITTINGGI TERDAHAP BEBAN GEMPA DENGAN METODE PUSHOVER ANALYSIS - Noviani Chandra, Indah; Masril, Masril; Nurhasanah Habirun, Asiya (Ensiklopedia Research and Community Service Review, 2024)
Indonesia is at the meeting of four tectonic plates called the Ring of Fire. The 2009 West Sumatra Earthquake occurred with a magnitude of 7.6 on the Richter Scale off the coast of Padang. The application of pushover analysis could be an anticipation and reference for construction organizers. The structure of the Wisma Mulya Syariah building is modeled according to the floor plan. The application of pushover analysis is guided by SNI Earthquake 1726:2019, and the pushover analysis method (ATC-40, 1996), so according to the calculations referring to ATC-40 the maximum total deviation and maximum inelastic deviation are declared to be included in the Immediate Occupancy (IO) category not exceeding a result of > 0.01 means that the building is still able to withstand the load of the earthquake that occurred with very little risk of loss of life.Keywords: Ring of Fire; earthquake; homestead; pushover analysis; Immediate Occupancy (IO).